Application on Power of Sale Deed based on Deed Recognition of Debt by A Notary Position - Saharuddin Saharuddin; Bambang Tri Bawono (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2022)
This study aims to determine and analyze the legal application of the selling power of attorney can still be based on the debt acknowledgment deed related to Decision Number 41/Pdt.G/2020/PN.Kdi. The research method used normative juridical approach with descriptive analytical research specifications. The types and sources of data in this study are secondary data consisting of: a. Primary Legal Materials; b. Secondary Legal Materials; c. Tertiary Legal Materials. Methods of collecting data through the Study of Literature and Documentation. While the data analysis method is a qualitative analysis method. The results of this study indicate that the application of the law to the deed of power of attorney in Decision Number 41/Pdt.G/2020/PN. Kdi can still be based on the deed of acknowledgment of debt because the deed is not absolute with Article 1813 jo. Article 1814 of the Civil Code concerning the termination of the power of attorney. The absolute nature of the power granted will have legal force if it explicitly contains the expression that what the plaintiff is empowered to do contains the phrase